2019
DOI: 10.2298/abs181120003t
|View full text |Cite
|
Sign up to set email alerts
|

Periphytic diatoms in the presence of a cyanobacterial bloom: A case study of the Vrutci Reservoir in Serbia

Abstract: Despite their unique ecology and implications for ecological assessment, diatoms in lentic ecosystems are still insufficiently studied in both scientific research and operational monitoring. In particular, the ecology of periphytic diatoms relative to the global expansion of cyanobacterial blooms in lakes has not been described at all. This study aims to describe the diversity and dynamics of a periphytic diatom community in the Vrutci Reservoir during Planktothrix rubescens bloom, and to evaluate the adequacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Encyonopsis microcephala is not a rare species and may be locally abundant, but it is taxonomically still not distinguished from similar taxa (Lange-Bertalot et al 2017). It was previously recorded for instance in Ohrid Lake, North Macedonia and Albania (Miho et al 2004), in lakes in Spain in epilithic communities (Blanco et al 2004), in benthos in Işıklı Lake, Turkey (Barinova et al 2014), in the Vrutci Reservoir, Serbia (Trbojević et al 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Encyonopsis microcephala is not a rare species and may be locally abundant, but it is taxonomically still not distinguished from similar taxa (Lange-Bertalot et al 2017). It was previously recorded for instance in Ohrid Lake, North Macedonia and Albania (Miho et al 2004), in lakes in Spain in epilithic communities (Blanco et al 2004), in benthos in Işıklı Lake, Turkey (Barinova et al 2014), in the Vrutci Reservoir, Serbia (Trbojević et al 2019).…”
Section: Discussionmentioning
confidence: 77%
“…A detailed review of Sava Lake's environmental parameters dynamic during this study period has already been reported (Jovanović et al, 2017, 2019 and these parameters were used in multivariate analyses, in terms of explaining the variability of diatom community composition and diatom indices.…”
Section: Resultsmentioning
confidence: 99%
“…The Sava Lake is a shallow urban reservoir (44°47 0 02.28 00 N, 20°23 0 25.64 00 E; 73 m a.s.l) formed in 1967 by embanking Sava river arm. Water volume of Sava Lake is about 4 000 000 m 3 , average depth is 4.5 m (maximum recorded 12 m), it is about 4.4 km long and about 250 m wide (Trbojević et al, 2017, 2019. Sava Lake is located in Belgrade, the capital city of Serbia.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Aneumastus species have been infrequently recorded on the Balkan Peninsula. Beside Lake Ohrid and Prespa (N. Macedonia, Levkov et al 2007), there is a single record in Serbia (Trbojević et al 2019) and in Croatia (Plenović-Moraj 1995). In the previous research on diatoms from Krka River two taxa have been recorded as Navicula pseudotuscula Hustedt and N. tuscula (Ehrenberg) Grunow (Plenović-Moraj 1995).…”
Section: Introductionmentioning
confidence: 99%